Managing a Symphony Orchestra in Times of Change: Behind the Curtains. (2018) - Bibu, Nicolae; Brancu, Laura; Teohari, Georgiana Alina
Abstract: The purpose of this paper is to discuss the symphony orchestra as a living organism in a perpetual interaction with the volatility of the nowadays environment, as a symbiosis between the goods and the services provided by a symphony orchestra's activity. A description of the symphony orchestra's activity, with emphasize upon German orchestras (Kulturorchester), as dominators on the classical symphony orchestras' market. This paper aims to present some of the mission statements, the goals, the good practices identified in symphony orchestras' management, mostly German, the typical and well-known pattern that characterizes a musician, member of an orchestra, and to describe the characteristics of today's management. There is a special emphasis placed on the interdisciplinary activity and the collaboration with the educational institutions. The results consist of the identification of the multiple stakeholders, the opportunities and the threats, the best practices and the innovative aspects in today's management of a symphony orchestra. "Tradition is not the worship of ashes, but the preservation of fire" Gustav Mahler